FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HERNIA INGUINAL DEWASA DI RSUD LABUHAN HALMAHERA SELATAN - Hidayat, Ferdian; Husen, Abd Hakim (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Inguinal Hernia disease begins due to the protrusion of an organ, tissue or structure through the wall of the cavity which normally contains these parts through the internal/lateral inguinal annulus tracing the inguinal canal and exiting the abdominal cavity through the external/medial inguinal annulus. This study aims to determine factors related to the incidence of adult inguinal hernias at Labuha Hospital, South Halmahera. This type of research is a case control design. The research sample was 46 respondents (23 cases and 23 controls) taken using the Accidental Sampling technique. Using the Chi-square test with a 95% confidence level. The research results show that the incidence of inguinal hernias in adults has risk factors such as obesity with an OR value = 16,923, work with an OR value = 12,960, chronic cough with an OR value = 110,250 and constipation with an OR value = 44,444.